Vitamin D deficiency and prevention: Turkish experience - BEREKET, ABDULLAH (WILEY-BLACKWELL, 2011)
A nationwide 'vitamin D prophylaxis augmentation programme' initiated in 2005 in Turkey reduced the prevalence of rickets from 6% in 1998 to 0.1% in 2008 in children under 3 years of age. The programme included free distribution of vitamin D drops to all new-borns and infants (0-12 months) visiting primary health stations throughout the country. Free disposal of vitamin D to infants is an effective strategy for preventing vitamin D-deficient rickets.
Keywords: Children; Cholecalciferol; Prophylaxis; Rickets; Turkey; Vitamin D; D SUPPLEMENTATION; D INTOXICATION; NUTRITIONAL RICKETS; INFANTS; ENVIRONMENT; CHILDREN; WOMEN; RISK